A pleiotropy scan to discover new susceptibility loci for pancreatic ductal adenocarcinoma - Giaccherini, Matteo; Rende, Mariaconcetta; Gentiluomo, Manuel; Corradi, Chiara; Archibugi, Livia; Ermini, Stefano; Maiello, Evaristo; Morelli, Luca; van Eijck, Casper H J; Cavestro, Giulia Martina; Schneider, Marton; Mickevicius, Antanas; et al. (Mutagenesis, 2025)
Pleiotropic variants (i.e. genetic polymorphisms influencing more than one phenotype) are often associated with cancer risk. A scan of pleiotropic variants was successfully conducted 10 years ago in relation to pancreatic ductal adenocarcinoma susceptibility. However, in the last decade, genetic association studies performed on several human traits have greatly increased the number of known pleiotropic variants. Based on the hypothesis that variants already associated with a least one trait have a higher probability of association with other traits, 61 052 variants reported to be associated by at least one genome-wide association study with at least one human trait were tested in the present study consisting of two phases (discovery and validation), comprising a total of 16 055 pancreatic ductal adenocarcinoma (PDAC) cases and 212 149 controls. The meta-analysis of the two phases showed two loci (10q21.1-rs4948550 (P = 6.52 × 10-5) and 7q36.3-rs288762 (P = 3.03 × 10-5) potentially associated with PDAC risk. 10q21.1-rs4948550 shows a high degree of pleiotropy and it is also associated with colorectal cancer risk while 7q36.3-rs288762 is situated 28,558 base pairs upstream of the Sonic Hedgehog (SHH) gene, which is involved in the cell-differentiation process and PDAC etiopathogenesis. In conclusion, none of the single nucleotide polymorphisms (SNPs) showed a formally statistically significant association after correction for multiple testing. However, given their pleiotropic nature and association with various human traits including colorectal cancer, the two SNPs showing the best associations with PDAC risk merit further investigation through fine mapping and ad hoc functional studies.
Keywords: duktální karcinom slinivky břišní; Genetic Predisposition to Disease; pancreatic cancer; single nucleotide polymorphism; Genetic Pleiotropy; Carcinoma, Pancreatic Ductal; genetic susceptibility; Genome-Wide Association Study; Case-Control Studies; jednonukleotidový polymorfismus; genetická pleiotropie; Pancreatic Neoplasms; pleiotropy; Polymorphism, Single Nucleotide; lidé; ženské pohlaví; studie případů a kontrol; Humans; nádory slinivky břišní; Female; genetická predispozice k nemoci; celogenomová asociační studie